Where the action is: Towards a discursive psychology of "authentic" identity in soccer fandom. (March 2016) - Miller, Paul K.; Benkwitz, Adam
Abstract: Objectives: Fandom underpins a wide range of foundational sporting activities. The corpus of psychological research on the topic remains, however, largely concerned with (a) producing of formal taxonomies of fans, and (b) making the analytic distinction between authentic "fans" and mere "spectators." This work is premised on the classical – but problematic – social-cognitive assumption that identity itself both precedes and (largely) determines the manner in which it is communicated. As such, the core objective of this paper is to take provisional empirical steps towards a formal psychology of "authentic" sporting fandom that does not replicate this troublesome assumption. Design: A Discursive Psychological framework is used to explore how self identified soccer fans make "robust" cases for the authenticity of their own fan-identities. Method: N = 26 unstructured interviews are analysed to highlight the constructive and attributional techniques drawn upon by speakers when making cases, and the culturally-available knowledges and contextual reasoning procedures that these make apparent. Results: Three models for legitimating fan-identity are described: (a) longitudinal endurance, (b) logical choice-making and (c) emotional imperative. It is noted how key issues that inform social-cognitive analysis are actually assembled as members' concerns in the service of persuasively accounting for particular claims in situ, and that this can facilitate a stronger understanding of the interrelation between sporting culture and social identity itself. Conclusions: Until a stronger description of public procedures for self-identification is advanced, analytic abstractions made for the sake of "clarity" can guarantee no relevance to the social psychological lives of everyday fans themselves. Highlights: Fans can legitimate their authenticity using a number of overlapping interpersonal techniques. Appeals to "through thick and thin" long-service are used. Appeals to having "actively realised" of what true fandom is are used. Appeals to being "emotionally determined" to support a team are used. All are used in the service of making particular orders of claim in situ .